CHEMICAL CONSTITUENTS AND IN VIVO PRELIMINARY EVALUATION OF THE TOXICOLOGICAL ACTIVITY OF Ouratea spectabilis (OCHNACEAE) AND Clitoria guianensis (FABACEAE) LEAVES - De Sousa, Frank Bruno Vieira; Cruz, Állefe Barbosa; Soares, Daniela Francisca; Cunha, Camila Luiza [UNESP]; Holzbach, Juliana C. (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2023)
Clitoria guianensis and Ouratea spectabilis, found in the Brazilian Cerrado, are used in folk medicine, despite the few chemical and biological studies reported in the literature. The present study aims to investigate the toxicity and effect of extracts from both species on the microcrustacean Artemia salina, and to determine the chemical composition of the hexane extract of O. spectabilis leaves and the EtOAc fraction of C. guianensis leaves. Kaempferitrin, a flavonoid isolated from of the EtOAc fraction of C. guianensis leaves, was identified by chemical analysis. Analysis of the hexane extract of O. spectabilis leaves using gas chromatography-mass spectrometry (GC-MS) suggested the presence of twenty-five known substances. The Hex, EtOAc, and EtOH crude extracts of C. guianensis leaves exhibited high and moderate toxicity against Artemia salina, with median lethal dose values (LD50) of 43.7, 25.4, and 233.4 mg.L−1, respectively. The acetone extract of O. spectabilis leaves showed moderate toxicity against Artemia salina with an LD50 value of 115.13 mg.L−1.
Keywords: Artemia salina; Cerrado; Kaempferitrin